Social Media Analysis as a Model for Internalizing Character ValuesLearners (Study at UPT SDI Karumpa Barat No. 105 Kep. Selayar) - Nur Hidayat; Muh. Tahir Malik; Asri Asri (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to analyze the moral values ​​of social media use, the model of internalization of character values, as well as the obstacles and challenges of utilizing social media as a vehicle for character formation of students at UPT SDI Karumpa Barat No. 105 Kepulauan Selayar. This study uses a qualitative research type with an ethnomethodological approach. Data collection techniques are carried out through interviews, observations, and documentation with key informants of students as well as key informants of teachers and principals. Data analysis uses the Miles and Huberman model through data reduction, data presentation, and drawing conclusions, while data validity testing is carried out through triangulation of sources, techniques, and time. The results of the study show that the moral values ​​of social media use of students are reflected through digital courtesy, social empathy, responsibility, cooperation, and digital communication ethics. The process of internalization of character values ​​takes place through digital role models of teachers, moral communication habits, value reinforcement, and digital social interactions of students. Obstacles and challenges of the study include low digital literacy of students, limited monitoring of digital activities, maintaining consistency of character behavior, and creating a positive and sustainable school digital culture.